1999
DOI: 10.1590/s1020-49891999000300002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de las infecciones por virus de las hepatitis B, C, D y E en Bolivia

Abstract: In Bolivia, no studies have been carried out specifically on hepatitis viruses. Thus, their prevalence and circulation patterns are virtually unknown. A seroepidemiologic study was performed from 1992 to 1996 to generate a preliminary idea of the overall prevalence of infection from hepatitis B, C, D, and E viruses (HBV, HCV, HDV, and HEV, respectively) in different Bolivian population groups. Prompted by the data obtained in other areas of Latin America, the study focused on indigenous communities in the Amaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
1
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 22 publications
5
22
1
5
Order By: Relevance
“…14 The overall observed prevalence is similar to the reported one in non-drug abusing prostitutes in Mexico City. 15 Nevertheless, the prevalence is lower than the reported one in some Latin American and Caribbean countries, 2 as has been notified in Brazil, 16 Bolivia, 9 Nicaragua, 17 Jamaica, 18 or Belize. 5,19 San Juanito could be considered as a low endemicity area of hepatitis B.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…14 The overall observed prevalence is similar to the reported one in non-drug abusing prostitutes in Mexico City. 15 Nevertheless, the prevalence is lower than the reported one in some Latin American and Caribbean countries, 2 as has been notified in Brazil, 16 Bolivia, 9 Nicaragua, 17 Jamaica, 18 or Belize. 5,19 San Juanito could be considered as a low endemicity area of hepatitis B.…”
Section: Discussionmentioning
confidence: 90%
“…5,9,10 Several studies have been conducted in Mexico, but most of them have been carried out in urban populations. No population-based prevalence study has been conducted so far in rural communities of Mexico; nor have they included indigenous inhabitants.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the Waorani have the highest HBV prevalence of any Amazonian group investigated to date. [1][2][3][4][7][8][9] Many investigators have sought to determine the modes of transmission of HBV, particularly in populations where it is hyperendemic. Vertical (perinatal) transmission alone would not be adequate to produce the high prevalence of HBV infection seen among the Waorani, since only 11% of reproductive age women appear to be carriers of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Serologic markers for HBV infection have been found at rates of 25 to 83% among Amazonian peoples in Bolivia, Brazil, Peru, and Venezuela. [1][2][3][4][5][6][7][8][9] A study of the Waorani, an indigenous people of the Amazon basin of Ecuador, reported antibodies to the Hepatitis B core (HBc) in 74% of people living in three villages, but none of those living in a fourth community. 10 Infection with hepatitis D virus (HDV) can only occur in individuals who are also infected with HBV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation